HUBUNGAN ASUPAN ZAT GIZI MIKRO DENGAN FUNGSI KOGNITIF PADA LANJUT USIA DI PAGUYUBAN AMONG YUSWA BANTENG BARU KABUPATEN SLEMAN - , Ade Rahmawati, dr. I Dewa Putu P., SpPD,K-Ger ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The number of elderly population in Indonesia has been increasing in the last two decades. This is followed by the increase of life expectancy from 66.7 years to 70.5 years. Increasing life expectancy will bring impact to the emergence of diseases in the elderly, one of them is degrading cognitive function. The degradation may disrupt productivity and daily activities and affect quality of life of the elderly. One aspect that affects cognitive function is intake of micronutrients (vitamin B6, folate, vitamin C, and vitamin E) that become an essential factor in the maintenance of cognitive function. He result of some studies show that adequate intake of vitamin B6, folate, vitamin C, and vitamin E will help in maintaining cognitive function. Objective: To identify association between intake of micronutrients (vitamin B6, folate, vitamin C, and vitamin E) and cognitive function of the elderly at Among Yuswa Club of Banteng Baru District of Sleman. Method: The study was observational with cross sectional design. Samples of the study were all elderly people at Among Yuswa Club of Banteng Baru District of Sleman. The study subjects were 99 elderly people. Data of cognitive function were obtained from the result of Mini Mental State Examination (MMSE) and intake of micronutrients from Semi Qualitative Food Frequency Questionnaire (SQFFQ). Bivariate analysis used chi square and multivariate used logistic regression. Result: The result of the analysis showed variables statistically had significant association with cognitive function were vitamin B6 (p=0.010